Synthesis and Characterization of Chitosan from Shrimp Shell Waste for Enhanced Oil Recovery - Akbari, Achmad
As a maritime country which has the fourth longest coastline in the world, Indonesia has a great potential marine resources. Shrimp is one of them which has a high economic value. However, it also produces shrimp shell waste which usage has to be optimized. On the other hand, the difficulties of finding new oil reservoirs in the world has endorsed scientists to optimize the old oil wells. The method used to increase the oil production is called EOR (Enhanced Oil Recovery) which is a tertiary technique to increase oil production from old wells by injecting chemicals such as polymer solution into the reservoir (polymer flooding). The objective of this research is to study the potency of shrimp shell waste as the basic polymeric material for EOR application. The first step done in this work was to synthesize chitosan from shrimp shell waste containing chitin by deacetylation process using NaOH 50% w/w. This process was performed through three stages to obtain a degree of deacetylation of 53% based on FTIR analysis. The viscosity measurement showed that the ????????? (viscosity average molecular weight) was about 1.22 x 106. The effect of temperature on the viscosity of the chitosan solutions had also been studied. It showed that the intrinsic viscosity of chitosan solution decreased at 70 °C. The viscosity of chitosan solutions with 1000-8000 ppm concentration at varied temperatures ranged between 70-100°C revealed that higher temperature resulted in lower viscosity. The rheology test at a shear rate of 511.2 s-1 showed that the viscosity of chitosan solutions was much lower than its of commercial polymer. Therefore, this result has to be developed further to increase the potency of chitosan for EOR application.